The not-so-great divergence: Asian and western world energy economy before 1815, and beyond - Moore , Nathan Matthias (Growth, 2025)
Here is an examination of Chinese institutional change and why the debate necessitates a new approach toward studying global economic divergence, one that focuses on a separation of historical mathematical evaluations rather than technological advancement. The Great Divergence debate is a historiographical discipline examining state formation in East Asia and its cultural evolution in juxtaposition with parts of Western Europe. The advent of steam power and other technologies in production and transport allowed Britain and others to extend their momentum past Malthusian restraints and separate themselves from "poorer" countries. But recently, the "California School" of historians like Bin Wong, Kenneth Pomeranz, and Andre Gunder Frank contend that China shared several similarities in proto-industrial development with their Western counterparts throughout Eurasia as late as 1750. My article will add impetus to an even newer argument by focusing on separate commentary from historians studying Europe’s transition to an Arabic numeral system and China’s insistence on traditional numeric methods. Modernity originated from a new abacus based on a ten-place system calculating numbers as large as 10^27, the year some purport it to have first been taught in Europe. Contemporary calculating devices and literacy materials are built on a similar model of arithmetic standards.